Sustainability assessment of pectin extraction from Citrus paradisi peel to support the encapsulation of lactic acid bacteria - Natalia A. Di Clemente; Enzo La Cava; Sonia Sgroppo; Andrea Gomez-Zavaglia; Esteban Gerbino (Applied Food Research)
Abstracts: Agro-industrial waste, including peels, pulps, pomace, and seeds, poses a significant global economic and environmental problem. Recovering these wastes to extract bioactive compounds (e.g., pectin, polyphenols, pigments, essential oils) offers a sustainable solution. Pectins are increasingly used as delivery systems in the food industry. Green extractions have been developed to reduce conventional methods' extraction time and environmental impact. However, little is known about their actual impact. Life Cycle Assessment (LCA) is a useful tool for assessing the environmental and energy impacts of a production cycle. This study aimed to evaluate the environmental profile of pectin extraction from grapefruit peels using conventional heating (CHE) and thermosonication (TS) methods, and the application of the extracted pectin as a delivery system for encapsulating Lactiplantibacillus plantarum CIDCA 83114. The LCA was performed using Open LCA software version 2.0.1 modeled with ILCD 2011 method. The system boundaries were considered to be laboratory scale and the functional units were 1 kg of freeze-dried encapsulated bacteria in pectin extracts from Citrus paradisi peel obtained by TS or CHE. The impact scores of the TS and CHE scenarios were similar in terms of millipoints (TS = 18.9 and CHE = 19.1 mPt). The main impact categories were climate change, human toxicity with carcinogenic effects and depletion of water resources contributing to deionized water and electricity consumption. The obtained results contribute to the decision-making process for the selection of a pectin extraction process on a laboratory scale, complemented by future economic impact studies.